The Effect of Combined Sprinting and Plyometric Training With Modified Circuits on Strength Endurance, Terminal Velocity, Aerobic Capacity, and 400m Performance in Under-20 Years - Abdel, Hussein Alawi; Hussein, Ali AbdulAmir; Attia, Mohammed Bajay (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The specificity of the 400m race requires runners to run at speeds close to their maximum. This places a significant role on the central nervous system, which is responsible for the continuous mobilization of muscle fibers when a large amount of lactate accumulates. Consequently, it must improve the efficiency of the nervous system to increase the mobilization of fast-twitch muscle fibers during high lactate accumulation within the muscles. This must also increase the ability of these fibers to generate the energy they need by removing and breaking down lactate during intensive training and competition. This is the key to developing a runner's ability to tolerate and handle lactate accumulation and produce high speed despite the large accumulation, which is a high indicator of the efficiency of the body's functional organs and systems. The study aimed to: 1. Identify the effect of combined running and plyometric exercises using modified circuits on strength endurance, final speed, aerobic capacity, and the 400m completion rate for under-20years. 2. Identify the superiority of the effect between the experimental and control groups in developing research variables. The researchers used the experimental approach, designing two equivalent groups: control and experimental, to suit the research objectives and hypotheses. The research population consisted of 16 runners from the Middle Euphrates Governorates (Karbala, Babil, Najaf, Diwaniyah) and the capital, Baghdad, in the 400m under-20 competition. The researcher randomly selected the 10 runners for his research sample, representing 62.5% of the research population. The most important conclusions of the researchers were: